Using a Single-Cube Beam-Splitter as a Fringe Pattern Generator Within a Structured-Light Projection System for Surface Metrology - Cordero-Carrasco, R; Leon-Rodriguez, M; Rayas, J (SPIE, 2017)
We show how a sinusoidal fringe pattern can be obtained by using a single cube beam splitter based on the Gates interferometer configuration. When an expanded and collimated laser beam hits the binding edge of a nonpolarizing cube beam splitter parallel to the splitter coating, it generates interference fringes at the exit due to the internal reflections and refractions of the laser beam passing through the cube. Unlike common digital projection systems, the proposed optical arrangement generates a perfectly sinusoidal and continuous fringe pattern, minimizing the problems associated with the discretization of a synthetic digital signal. The fast Fourier transform and phase-shifting techniques are used to demodulate the captured fringe patterns. Experimental results are presented for the three-dimensional shape reconstruction of the relief of a coin and of a spherical indentation on a piece of aluminum with a maximum height of about 150 μm. In addition, we evaluate the accuracy and resolution of the proposed measuring device: shape reconstruction accuracy is about 1.4% and axial resolution is 0.15 μm. Due to its simple and compact setup, the proposed system is particularly suited to be miniaturized. © 2017 Society of Photo-Optical Instrumentation Engineers (SPIE).